2023
DOI: 10.1161/circulationaha.122.061516
|View full text |Cite
|
Sign up to set email alerts
|

Peptide Vaccine Against ADAMTS-7 Ameliorates Atherosclerosis and Postinjury Neointima Hyperplasia

Abstract: BACKGROUND: The metalloprotease ADAMTS-7 (a disintegrin and metalloproteinase with thrombospondin type 1 motif 7) is a novel locus associated with human coronary atherosclerosis. ADAMTS-7 deletion protects against atherosclerosis and vascular restenosis in rodents. METHODS: We designed 3 potential vaccines consisting of distinct B cell epitopic peptides derived from ADAMTS-7 and conjugated with the carrier protein KLH (keyhole limpet hemo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 54 publications
1
21
0
Order By: Relevance
“…Consequently, ADAMTS7 antibodies raised against the ADAMTS7 catalytic domain protected against stent-induced restenosis in a preclinical swine model. 24,25 Furthermore, high ADAMTS7 levels were identified in heart tissue 20 and injured vessels, 18 which is in line with the CAD protection conferred by the low risk allele and the intimal thickening induced by the high risk allele as detailed above. Collectively, the data suggest that ADAMTS7 inhibition might be a new way to treat CAD and restenosis.…”
Section: ■ Introductionsupporting
confidence: 65%
“…Consequently, ADAMTS7 antibodies raised against the ADAMTS7 catalytic domain protected against stent-induced restenosis in a preclinical swine model. 24,25 Furthermore, high ADAMTS7 levels were identified in heart tissue 20 and injured vessels, 18 which is in line with the CAD protection conferred by the low risk allele and the intimal thickening induced by the high risk allele as detailed above. Collectively, the data suggest that ADAMTS7 inhibition might be a new way to treat CAD and restenosis.…”
Section: ■ Introductionsupporting
confidence: 65%
“…9,10 Ma et al 4 generated a vaccine targeting ADAMTS-7 using 3 epitopes of its secondary structure at the catalytic domain as well as the C-terminal thrombospondin (the "TS" in ADAMTS) repeats. 4 This is important because the catalytic domain was recently identified to be critical for the role of ADAMTS-7 in atherosclerosis, 10 and the thrombospondin repeats are known to bind its targets COMP and thrombospondin-1. 7,8 The authors were able to induce an immune response against these epitopes and subsequently studied the efficacy in vascular diseases.…”
Section: Article See P 728mentioning
confidence: 99%
“…8 Assuming that the mechanisms affected by vaccination against ADAMTS-7 are better understood, such treatment needs to demonstrate an excellent safety profile, as novel strategies for prevention of atherosclerosis or treatment of its complications might be of relevance for large patient groups. Ma et al 4 observed no safety issues of ATS7vac, which nevertheless needs to be complemented by robust testing in other models before treatment of patients can be considered.…”
Section: Article See P 728mentioning
confidence: 99%
See 1 more Smart Citation
“…9 Recently, in an experimental study, vaccination against ADAMTS-7 successfully reduced atherosclerotic plaque formation under proatherogenic conditions and prevented neointima formation and in-stent restenosis. 10 The effects of ADAMTS-7 on vascular remodeling can be explained by degradation of the substrate COMP (cartilage oligomeric matrix protein), 11 which was also found to mediate ADAMTS-7-related effects in rheumatoid arthritis and represents its first known substrate. Another binding partner of ADAMTS-7 is THBS1 (thrombospondin-1 or TSP1).…”
mentioning
confidence: 99%